Drug trafficking - Bauder, Julia (Detroit : Greenhaven Press, 2008)
Contains twenty-six essays that offer varying perspectives on issues related to drug trafficking, including how and if it should be stopped, the effects on the United States of stopping drug trafficking, the War on Drugs and Latin America, and the War on Terror; and provides contact information for organizations and a bibliography.
Includes bibliographical references (p. 242-246) and index.
Young Adult
Keywords: Narcotics control; Drug traffic -- United States